Correcting inequity: How the implementation of the Kasigau Corridor REDD+ Project in fact redresses past injustices—Response to Chomba et al. (30th November 2016) - Githiru, Mwangi
Abstract: Chomba et al. recently examined at how present day actions can reinforce or aggravate historical injustices around land, and what should be done about it. The authors looked at the benefit distribution policy and practice of the Kasigau Corridor REDD+ Project (KCRP) in Kenya, with the aim of understanding the extent to which it addressed equity, particularly with respect to historical injustices concerning land in Kenya. We agree with Chomba et al. that land tenure in Kenya has involved dispossession enabled by colonial and post-colonial land policies, which left many local people with little or no land entitlement. However, we strongly disagree with them when they argue that because the revenue distribution policy of the KCRP mapped onto the existing land distribution, it automatically reinforced inequality. In this response, we will highlight several important inaccuracies in their paper that may give a false impression of the KCRP, then broach some of these genuine and pressing land-related issues which we felt Chomba et al. missed out elaborating on, which would have helped inform future policy around payment for environmental services schemes in Kenya and elsewhere.